1981
DOI: 10.1207/s15327906mbr1602_7
|View full text |Cite
|
Sign up to set email alerts
|

Associations Between Violent And Nonviolent Criminality: A Canonical Contingency-Table Analysis

Abstract: Frequencies of violent and nonviolent convictions among 390 adult, male offenders were cross-tabulated, dummy coded, and analyzed by canonical correlation. Though of small magnitude, a statistically significant dimension of association between violent and nonviolent criminality was obtained, and the nature of this relationship was ascertained by means of intraset and interset structure coefficients and an index of interset redundancy. The results, weakly supportive of the crime specialization hypothesis, were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
6
0

Year Published

1982
1982
2012
2012

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 4 publications
1
6
0
Order By: Relevance
“…Delinquent behaviors are not all alike. The nature of the delinquency and the etiological history of the offender can vary greatly (Gerstein & Briggs, ; Holland, Levi, & Beckett, ). Thus, juvenile violent and non‐violent probationers examined in this study varied to a large extent in terms of their psychological characteristics.…”
Section: Discussionsupporting
confidence: 92%
“…Delinquent behaviors are not all alike. The nature of the delinquency and the etiological history of the offender can vary greatly (Gerstein & Briggs, ; Holland, Levi, & Beckett, ). Thus, juvenile violent and non‐violent probationers examined in this study varied to a large extent in terms of their psychological characteristics.…”
Section: Discussionsupporting
confidence: 92%
“…The advantage of this approach criminologically is that offenders are allowed to change type if they are criminally active in more than one five-year period. This therefore addresses the criticisms of typologies by Figlio (1981) and Holland et al (1981). The five-year period is, however, long enough to be able to gain an understanding of the typology of an offender if he or she is offending within that period.…”
Section: Typologies Of Offendingmentioning
confidence: 57%
“…The development of such criminal typologies has had dissenting voices. One suggested that static typologies do not reflect the fact that criminal activity appears to vary over time (Figlio 1981;Holland et al 1981). In contrast, Gibbons (1975), an erstwhile exponent in the 1960s, later suggested that, for most existing typologies, it was difficult to allocate individuals unambiguously to types in a real-life setting.…”
Section: Typologies Of Offendingmentioning
confidence: 99%
“…CCA, which has found its application of analysing variable interrelationships in fields as diverse as biometrics [42,43], economics [44], social sciences [45] and criminology [46], proved to be the most successful algorithm in identifying the least significant terms in the model for both the predictor and response variables, by using both the information from the weight vectors and from the residuals of both the predictor and response terms.…”
Section: Discussionmentioning
confidence: 99%